Guidance for the Development and Review of ANPR Infrastructure : To support the consistent and proportionate deployment of ANPR Infrastructure by the Police and other Law Enforcement Agencies.: To support the consistent and proportionate deployment of ANPR Infrastructure by the Police and other Law Enforcement Agencies. (2021) - Unknown
No abstract available